2015
DOI: 10.1200/jco.2014.59.5728
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Li-Fraumeni Syndrome From TP53 Mutation Carriers

Abstract: The clinical gradient of the germline TP53 mutations, which should be validated by other studies, suggests that it might be appropriate to stratify the clinical management of LFS according to the class of the mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
585
5
12

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(634 citation statements)
references
References 39 publications
32
585
5
12
Order By: Relevance
“…Our results are consistent with those of Bougeard et al who, in a study published in 2015, conducted on 127 breast cancer patients and positive TP53 mutations reported that HER 2 alone was positive in 55% of cases and 37% of cases were triple positive [31].…”
Section: Tp53supporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with those of Bougeard et al who, in a study published in 2015, conducted on 127 breast cancer patients and positive TP53 mutations reported that HER 2 alone was positive in 55% of cases and 37% of cases were triple positive [31].…”
Section: Tp53supporting
confidence: 93%
“…This observation is supported by other studies that have shown that breast cancer patients with positive TP53 mutation can associate HER2 -overexpressing forms in up to 82% of cases [30,31].…”
Section: Tp53supporting
confidence: 83%
“…In a recent report on 322 TP53 mutation carriers from French Li -Fraumeni families, the mean age of tumor onset was statistically different between carriers of missense mutations (23.8 years) and those carrying nonsense mutations or genomic rearrangements (28.5 years). The difference was even larger when comparing hotspot mutations, such as p.R175H or p.R248W (mean age of tumor onset, 15 -20 yr) with complete deletion of the TP53 gene (38.5 yr) (Bougeard et al 2015). Assuming that complete deletion of TP53 represents a "straight" LOF effect, these observations suggest that the more severe clinical phenotype of hotspot mutants is caused by their capacity to impair the wild-type allele (DN effects) and/or by specific GOF effects.…”
Section: Classifying Tp53 Mutations For Clinical Usementioning
confidence: 97%
“…Therefore, large-scale studies on the precise clinical significance of TP53 variants in introns and alternative exons are now required to improve our understanding of the significance of these regions (Box D). In the meantime, a pragmatic recommendation would be to consider the entire sequence of the TP53 gene for mutation screening strategies using NGS in sporadic cancers as well as in the germline of subjects who meet the criteria for TP53 mutation testing (80)(81)(82). …”
Section: Discussionmentioning
confidence: 99%